Vectorial Doppler metrology - Liang Fang (Nature Portfolio, 2021)
The Doppler effect is a wave phenomenon that can find the magnitude of velocity of moving targets with scalar waves. Here, the authors use vectorially structured light with spatially variant polarization to fully determine both the magnitude of velocity and motion direction of a moving particle.